Effect of the thickness of concrete cover on the fatigue bond strength of GFRP wrapped and non-wrapped reinforced concrete beams containing a lap splice. (May 2016) - Alyousef, Rayed; Topper, Tim; Al-Mayah, Adil
Abstract: Lap splices are a common construction method for joining steel rebars in reinforced concrete beams because of their simplicity and low cost. The bond strength between the concrete and reinforcing bars in a splice is crucial to many aspects of the behaviour of a reinforced concrete member. Fatigue flexural loading imposes severe demands on the strength and ductility of the lap splice region in reinforced concrete structures and can lead to a brittle and sudden failure of the member. This paper investigates the effect of different concrete covers on the fatigue bond strength of reinforcing concrete beams containing a lap splice under a fatigue loads. It includes tests of twenty two beams divided into two groups. Each group has beams with 30 mm and 50 mm clear side and bottom concrete covers. The variables that were addressed where the concrete cover, the presence or absence of GFRP sheet wrapping, the type of loading (monotonic or fatigue) and the fatigue load ranges. The test results showed that an increase in the concrete cover led to an increase in the bond strength under both monotonic and fatigue loading for both the unwrapped and GFRP wrapped beams. Also, the GFRP sheets increased both the fatigue strength and the deflection for both the 30 mm and the 50 mm concrete covers.